Spatial patterns of boom and bust forestry investment development: A case study from Western Australia. (July 2019) - Nery, Thayse; Polyakov, Maksym; Sadler, Rohan; White, Ben
Highlights: Land use policies have had a strong bearing on landscape patterns. Rapid expansion of plantation forest due to tax benefits for MIS forestry. Reforestation policies are vulnerable to legislative changes of tax rulings. Tax-effective schemes should be grounded in sound market principles to avoid failure. Abstract: Land use policies interact with biophysical and socioeconomic characteristics to determine land use and land cover (LULC) changes. This paper presents a method for assessing the determinants of plantation land use transitions from 1979 to 2014 from Landsat data for the Warren River Catchment (4, 416 km 2 ) in Western Australia. This catchment is intrinsically interesting because it is a frontier between agriculture, high biodiversity native forests and commercial forest plantations. Further land use policies have had a strong bearing on LULC. Initial forest clearing in the catchment was the result of agricultural development policy. It was followed by the ban on clearing native vegetation on private land in 1978. The Management Investment Scheme introduced in the 1990s led to a rapid increase in the area of plantation forest on agricultural land. The catchment has two significant environmental problems: first dryland salinity leading to land degradation and the salinization of rivers and streams; and second the protection of high levels of endemic biodiversity. LULC changes from 1979 to 2014 reveal that soil depth, distance to urban centres, surrounding land use, and private land are positively correlated with transitions to plantation forest. The Management Investment Scheme brought the largest changes in LULC as land transitioned into Eucalyptus plantations in the 1990s when the tax incentives were introduced and then gradually out of plantations by clear-felling and conversion to agriculture as tax benefits for the scheme were reformulated and uncertainty about the policy increased. Other evidence on policy effects are that the Forest Management Plans have sustained the area of native forest and the ban on clearing has been effective.